2001
DOI: 10.1073/pnas.051629698
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assembly of phytochrome B apoprotein with synthetic analogs of the phytochrome chromophore

Abstract: Phytochrome B (PhyB), one of the major photosensory chromoproteins in plants, mediates a variety of light-responsive developmental processes in a photoreversible manner. To analyze the structural requirements of the chromophore for the spectral properties of PhyB, we have designed and chemically synthesized 20 analogs of the linear tetrapyrrole (bilin) chromophore and reconstituted them with PhyB apoprotein (PHYB). The A-ring acts mainly as the anchor for ligation to PHYB, because the modification of the side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 53 publications
2
24
0
1
Order By: Relevance
“…Although it is tempting to speculate on the existence of PCB in higher plants, this has not been identified. Interestingly, the binding efficiency of various bilins to recombinant PHYB was determined in vitro, with the result that PCB bound to PHYB more efficiently than P⌽B (21). In the present work, we found that PCB and P⌽B restore PhyB-mediated physiological responses.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Although it is tempting to speculate on the existence of PCB in higher plants, this has not been identified. Interestingly, the binding efficiency of various bilins to recombinant PHYB was determined in vitro, with the result that PCB bound to PHYB more efficiently than P⌽B (21). In the present work, we found that PCB and P⌽B restore PhyB-mediated physiological responses.…”
Section: Discussionsupporting
confidence: 53%
“…R͞FR and FR͞R were generated by using a custom-built LED irradiation system, as previously reported (11 Bilin Preparation. PCB (18), P⌽B (17), and their analogs (21,29) were chemically synthesized, as reported. The bilins were stored as 2 mM stock solutions in dimethyl sulfoxide under nitrogen atmosphere at Ϫ80°C.…”
mentioning
confidence: 99%
“…10), including natural PÈB and PCB, and reconstituted them with recombinant Arabidopsis PhyB apoprotein (PHYB) through collaborative study with biologists. 125 The difference absorption spectra of the in vitro-assembled adducts of the synthetic bilin chromophores with PHYB were measured on actinic far-red and red light irradiations. The adduct with PCB showed a similar difference spectrum to that of the PÈB adduct, although its peaks were slightly blue shifted due to the difference of the length of -conjugation system when compared with the PÈB adduct corresponding to the natural phytochrome, [137][138][139] as shown in Fig.…”
Section: Assembly Of the Synthetic Bilin Chromophoresmentioning
confidence: 99%
“…As mentioned above, we established an efficient and flexible synthetic method of various kinds of bilin chromophores, [46][47][48][49][50][51] including PÈB, 49 PCB, 47,48 and more than 20 kinds of PCB derivatives, 50,51 in free acid forms, which made it possible to assemble them with the apoproteins not only in vitro to analyze the spectral properties of the resulting holoproteins, 125 but also in vivo to observe their physiological functions 126 as will be seen later.…”
mentioning
confidence: 99%
See 1 more Smart Citation